10 Impaired stress myocardial oxygenation precedes contractile abnormalities in three models of cardiac hypertrophy: insights from a novel oxygen sensitive cardiac magnetic resonance approach. (28th January 2023) - Abid Akhtar, Mohammed; Mohiaddin, Hasan; Yeoh, Boon-Seng; Levelt, Eylem; Watkins, Hugh; Mahmod, Masliza; Neubauer, Stefan; Raman, Betty
Abstract : Introduction: Cardiac hypoxia is a key cause of myocardial dysfunction, but remains under-investigated due to challenges with direct myocardial oxygen assessment. Fast low flip angle short (FLASH) normalised blood-oxygen level-dependent cardiovascular magnetic resonance (nBOLD CMR) is a novel oxygen-sensitive CMR approach which allows for precise measurement of myocardial oxygenation. 1 We sought to a) characterise myocardial oxygenation in three models of hypertrophy: genetic – non-obstructive hypertrophic cardiomyopathy (nHCM); metabolic – Type 2 diabetes (T2DM); structural – severe Aortic Stenosis (SevAS) using nBOLD CMR and b) evaluate its potential for detecting oxygenation impairment in relation to contractile and perfusion abnormalities. Materials and Methods: 113 participants including healthy controls (n=30), T2DM (n=29), nHCM (n=29), and severe AS (n=24) underwent cine, adenosine stress nBOLD CMR, first pass perfusion imaging and late gadolinium (LGE) CMR. Stress oxygenation, absolute myocardial blood flow (MBF) and global longitudinal strain (GLS) were evaluated in all patients. Results: nHCM and SevAS had significantly thicker and fibrotic myocardium compared to controls and T2DM. Hyperaemic MBF was severely impaired in nHCM and SevAS (nHCM 2.1±0; SevAS 1.7±0.5mL·min −1 ·g −1 ) relative to controls (3.0±0.9 mL·min −1 ·g −1 ; p <0.001), but to a lesser extent in T2DM (T2DM 2.6±0.7 mL·min −1 ·g −1 ; p=0.03). Stress oxygenation was significantly reduced in T2DM, nHCM and SevAS, with further differences seen between T2DM and nHCM, (CON 17.4±2.1%; T2DM 12.5±4.8%; nHCM 8.34±4.5%; SevAS 9.18±6.5%; p <0.0001, figure 1 ). Among patients, 67% had normal contractility (GLS<-15% and LVEF >52%), and 54% had preserved perfusion (segmental stress MBF>1.4 mL·min −1 ·g −1 ). Stress oxygenation was impaired even among patients with preserved contractility (p=0.005) and perfusion (p<0.001) versus controls. Discussion: This is the first application of nBOLD CMR in severe AS and T2DM. T2DM had impaired myocardial oxygenation even in the presence of mild/no perfusion abnormalities, consistent with inefficient oxidative metabolism. nHCM and severe AS shared similarly blunted perfusion and oxygenation. Myocardial deoxygenation precedes contractile and perfusion abnormalities in hypertrophied hearts, highlighting the potential for stress BOLD to detect subclinical metabolic and perfusion abnormalities in cardiac diseases. Conclusion: nBOLD CMR is a promising, precise, and contrast-agent free tool to characterise myocardial oxygenation in a diverse range of cardiovascular diseases with a potential to enhance current diagnostic and prognostic algorithms. Reference: Raman B, Tunnicliffe EM, Chan K, Ariga R, Hundertmark M, Ohuma EO, Sivalokanathan S, Tan YJG, Mahmod M, Hess AT, Karamitsos TD, Selvanayagam J, Jerosch-Herold M, Watkins H, Neubauer S. Association Between Sarcomeric Variants in Hypertrophic Cardiomyopathy and Myocardial Oxygenation: Insights From a Novel Oxygen-Sensitive Cardiovascular Magnetic Resonance Approach. Circulation . 2021 Nov 16;144(20):1656–1658. doi: 10.1161/CIRCULATIONAHA.121.054015. Epub 2021 Nov 15. PMID: 34780254.